Do Pre-Training and Post-Training Factors Impact IT Training Transfer to the workplace? A Case Study from a Multinational Company in the UAE - Alaydie, Nada Naser (2016)
The purpose of this study is to investigate and provide insights about the extent to which pre-training and post-training factors play a role in influencing the IT training transfer to the workplace. The study looks at the subject in the context of corporate-sponsored IT training and education initiatives. In order to provide a framework and clarity in the case, this study examined the "as-is" state of IT training transfer to the workplace for participants of IT training who work for a multinational company in Dubai. An extensive review of research about the factors affecting the transfer of training to the workplace was conducted. The research had a specific focus on the effect of pre-training and post-training factors on IT training transfer. This resulted in the development of a research model for the IT training transfer process. All components of the model were measured by the means of a questionnaire for the IT training participants who attended a training 3-18 months before the study. Various types of statistical analyses techniques were used to examine the relationships in the model. The results indicate that pre-training and post-training factors significantly influence IT training transfer to the workplace. Factors related to post-training support and encouragement are more strongly related to IT training transfer than the factors related to pre-training activities. The further research implication of these findings is to translate these factors into training process activities and strategies that also incorporate the strengths of the findings of various learning theories. The concluding recommendations include a plan for improving the training process in order to improve the transfer of training in organizations.